Deciphering genetic characteristics of South China and North China indigenous pigs through selection signatures - Yahui Gao; Xueyan Feng; Shuqi Diao; Yuqiang Liu; Zhanming Zhong; Xiaotian Cai; Guangzhen Li; Jinyan Teng; Xiaohong Liu; Jiaqi Li; Zhe Zhang (BMC Genomics)
Abstract Background Indigenous pig breeds in China have accumulated significant genetic diversity due to regional selection pressures. Investigating the selection signatures of these populations helps to understand their adaptive evolution and contributes to genetic improvement programs. Results We collected whole-genome sequencing data from 133 individuals, including South China and North China indigenous pigs and Asian wild boars. After data filtering, we retained 31,521,978 high-quality SNPs. Population structure analysis using PCA revealed distinct genetic clustering among these populations. Selection signature detection identified 5,227 loci under selection in South China indigenous pigs and 5,800 in North China indigenous pigs compared to Asian wild boars. Candidate genes were enriched in immune response pathways, reproductive traits, and pigmentation pathways. South China indigenous pigs exhibited selection signals for fat deposition and immune responses, while North China indigenous pigs showed stronger signals related to growth, blood physiology, and reproductive performance. Additionally, key genes such as MC1R and KIT were associated with coat color variation, and IGF1R and IGF2R were linked to growth regulation. Conclusion Our results demonstrate that indigenous pigs in China have undergone selection for distinct traits aligned with their regional environments and farming systems. South China indigenous pigs have been selected for traits related to fat deposition and immunity, while North China indigenous pigs have been selected for growth and reproductive traits. The findings offer crucial insights into the genetic architecture of indigenous pig breeds, providing a valuable foundation for future genetic breeding programs.